Automatic crossbow control in industrial hot-dip galvanizing lines. (February 2023) - Marko, L.; Kugi, A.; Steinboeck, A.
Abstract: In industrial hot-dip galvanizing lines, the crossbow flatness defect of steel strips constitutes one of the main sources for coating thickness deviations and inhomogeneities. In this work, a novel algorithm for online minimization of the crossbow flatness defect based on the automatic adjustment of the pot roll intermesh is developed. The devised model-free control algorithm can be easily implemented on an industrial programmable logic controller, even with very limited computational resources. The controller uses measurement data from an electromagnetic strip stabilization device and avoids the use of the delayed measurement data from the downstream radiometric coating thickness gauges. Assuming that a hot-dip galvanizing line is already equipped with an electromagnetic strip stabilization device, additional hardware is not required for implementation. The control algorithm can also be easily adapted to processing lines without an electromagnetic strip stabilizer. A detailed stability analysis allows to derive some basic guidelines to guarantee the convergence of the overall control scheme. A short- and long-term evaluation of measurement results from an industrial hot-dip galvanizing line demonstrates the effectiveness and robustness of the proposed control scheme.